2015
DOI: 10.1111/jpn.12329
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, nitrogen degradability and in vitro ruminal biological activity of tannins in vines harvested from four tropical sweet potato (Ipomoea batatas L.) varieties

Abstract: This study investigated the potential of vines from four sweet potato varieties (Tia Nong 57, Tia Nong 66, Ligwalagwala and Kenya) as alternative feed resources for ruminant livestock. The chemical composition [neutral detergent fibre (NDF), acid detergent fibre (ADF), crude protein (CP) and acid detergent insoluble nitrogen (ADIN)], in vitro ruminal nitrogen (N) degradability and in vitro ruminal biological activity of tannins in the vines, harvested at 70 and 110 days after planting (DAP), were determined. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Other studies have demonstrated similar trends. Three of four cultivars compared in Swaziland decreased from an average CP of 190 g kg −1 DM at 70 DAP to 140 g kg −1 DM at 110 DAP . The CP of the C‐15 vines decreased from 175 g kg −1 DM at 60 DAP to 122 g kg −1 DM at 165 DAP .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Other studies have demonstrated similar trends. Three of four cultivars compared in Swaziland decreased from an average CP of 190 g kg −1 DM at 70 DAP to 140 g kg −1 DM at 110 DAP . The CP of the C‐15 vines decreased from 175 g kg −1 DM at 60 DAP to 122 g kg −1 DM at 165 DAP .…”
Section: Resultsmentioning
confidence: 96%
“…Five cultivars grown in different regions of Ghana had fresh vine yields ranging from 8 to 28 t ha −1 , with an average of 12 t ha −1 in the coastal region and 22 t ha −1 in the forest region . Four cultivars grown in Swaziland had fresh yields ranging from 24 to 57 t ha −1 at 90 DAP, while the same four cultivars produced 52–144 t ha −1 at 110 DAP . Yields reported on a DM basis include two cultivars grown in the Turrialba Valley of Costa Rica, which produced 3–4 dry t ha −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated in our previous study that sweet potato vines have the potential to be an alternative feed resource for ruminants (Ali et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Sweet potato is known to contain antinutritional factors, such as condensed tannins (Phale and Madibela ), which have been reported to interfere with ruminal nitrogen (N) degradability (Ali et al . ). Preserving tannin‐containing forages may reduce the concentration as well as the biological activity of condensed tannins thereby improving the feed value of the silage.…”
Section: Introductionmentioning
confidence: 97%